Improved Electrochemical Oxidative Degradation of Reactive Red 24 Dye by BDD Anodes Coupled with Nitrate. Issue 3 (1st March 2022) - Tang, Yining; He, Deliang; Guo, Yanni; Shang, Jun; Zhou, Lei; Pan, Rong; Dong, Wei; Liu, Mengli
Abstract : It is novelty proposed to use electrochemical oxidation (EO) coupled with BDD anode and nitrate to improve Reactive Red 24 (RR24) removal efficiency in wastewater treatment. The effects of operating parameters in the EO-NO3 − /SO4 2− system on the decolorization efficiency of RR24 were discussed, and the optimal operating parameters were obtained. The energy consumption for 100% decolorization within 15 min is 0.92 kWh m −3, and the total organic carbon (TOC) reaches 51.35% within 90 min. The degradation efficiency is excellent and energy saving. Through the effect of quenchers on RR24 decolorization efficiency, various active species in the EO process were studied. It was found that OH was closely related to the decolorization degradation of RR24, reaching a contribution rate of 99.47%. This is due to the catalytic effect of NO3 −, which greatly increases the generation rate of OH. Finally, we propose the degradation pathways of RR24 by UV–vis spectrum and HPLC-MS test, indicating that the azo bond is broken first, then the C–N bond between the benzene or naphthalene ring and the triazine ring is broken until it is mineralized to H2 O and CO2 . Therefore, it an efficient and environmentally friendly combined oxidation technology to degrade RR24 dye wastewater.